2014
DOI: 10.5194/hess-18-2257-2014
|View full text |Cite
|
Sign up to set email alerts
|

Synchronicity of historical dry spells in the Southern Hemisphere

Abstract: Abstract.A shift in climate occurred during the mid-1970s

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Other important spatial aspects of drought are synchronicity, clustering and breaking up of drought clusters. Most studies focused on spatial aspects of meteorological drought e.g., Refs 146,147; there has been relatively limited research on the spatial aspects of hydrological drought. One of the first clustering methods suitable for hydrological drought is the algorithm developed by Andreadis et al 148 for droughts in soil moisture and runoff in the USA.…”
Section: Hydrological Drought Scales and Spatial Characteristicsmentioning
confidence: 99%
“…Other important spatial aspects of drought are synchronicity, clustering and breaking up of drought clusters. Most studies focused on spatial aspects of meteorological drought e.g., Refs 146,147; there has been relatively limited research on the spatial aspects of hydrological drought. One of the first clustering methods suitable for hydrological drought is the algorithm developed by Andreadis et al 148 for droughts in soil moisture and runoff in the USA.…”
Section: Hydrological Drought Scales and Spatial Characteristicsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the four most influential climate modes on SEA's climate are -El Niño-Southern Oscillation (ENSO; Chiew et al, 1998;Kiem and Franks, 2001;Verdon et al, 2004) -ENSO is represented by the Oceanic Niño Index (ONI) from the United States National Oceanic and Atmospheric Administration (NOAA) Climate Prediction Centre (CPC) (www.cpc.ncep.noaa.gov). The ONI is a 3-month running mean of ERSST.v3b SST anomalies in the Niño 3.4 region, centred on 30-year base periods updated every 5 years.…”
Section: Role Of Large-scale Climate Phenomena In Driving Enhanced Autumn and Winter Rainfall During The Mid-1980s To The Early 1990s In mentioning
confidence: 99%
“…-Interdecadal Pacific Oscillation (IPO; Power et al, 1999;Kiem et al, 2003;Verdon et al, 2004;Power and Colman, 2006) -Both the raw and the smoothed time series of Power et al (1999) are used in this study in order to identify epochs of positive and negative IPO.…”
Section: Role Of Large-scale Climate Phenomena In Driving Enhanced Autumn and Winter Rainfall During The Mid-1980s To The Early 1990s In mentioning
confidence: 99%
“…Indeed, because the mismatch between modeled and observed per-capita consumption was highest at 5−11 year cycles (e.g., between 0.09 and 0.2 cpy, Figure S6), the following climate modes warrant further evaluation: the El Nino Southern Oscillation (ENSO; 3−7 year return period) and the Indian Ocean Dipole (IOD; 6−17 year return period). 77 Interactions among climate modes (e.g., ENSO, IOD, the Interdecadal Pacific Oscillation, and the Southern Annular Mode) should also be evaluated, as the relationship among modes shifted mid1970s, changing drought dynamics 78 (and potentially, urban water consumption) in the Southern Hemisphere.…”
mentioning
confidence: 99%